Periodontal outcomes and social, racial and gender inequalities in Brazil: a systematic review of the literature between 1999 and 2008 - João Luiz Bastos; Antonio Fernando Boing; Karen Glazer Peres; José Leopoldo Ferreira Antunes; Marco Aurélio Peres (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study was to review the Brazilian epidemiologic literature on periodontal outcomes and socio-demographic factors, assessing bibliographic and methodological characteristics of this scientific production, as well as the consistency and statistical significance of the examined associations. A systematic review was carried out in six bibliographic sources. The review was limited to the period between 1999 and 2008, without any other type of restriction. Among the 410 papers identified, 29 were included in the review. An increasing number of articles, specifically in the last four years of study, was observed. However, there is a concentration of studies in the South and Southeast regions of Brazil, and many of them are not closely connected to theoretical formulations in the field. In spite of these shortcomings, the review findings corroborate the idea that poor socioeconomic conditions are associated with periodontal outcomes, as demonstrated primarily by income and schooling indicators.